Glandular dose in breast computed tomography with synchrotron radiation. (18th December 2015) - Mettivier, G; Fedon, C; Di Lillo, F; Longo, R; Sarno, A; Tromba, G; Russo, P
Abstract: The purpose of this work is to provide an evaluation of the mean glandular dose (MGD) for breast computed tomography (CT) with synchrotron radiation in an axial scanning configuration with a partial or total organ volume irradiation, for the in vivo program of breast CT ongoing at the ELETTRA facility (Trieste, Italy). A Geant4 Monte Carlo code was implemented, simulating the photon irradiation from a synchrotron radiation source in the energetic range from 8 to 50 keV with 1 keV intervals, to evaluate the MGD. The code was validated with literature data, in terms of mammographic normalized glandular dose coefficients (DgN) and with ad hoc experimental data, in terms of computed tomography dose index (CTDI). Simulated cylindrical phantoms of different sizes (diameter at phantom base 8, 10, 12, 14 or 16 cm, axial length 1.5 times the radius) and glandular fraction by weight (0%, 14.3%, 25%, 50%, 75% and 100%) were implemented into the code. The validation of the code shows an excellent agreement both with previously published work and in terms of DgN and CDTI measurements. The implemented simulations show a dependence of the glandular dose estimate on the vertical dimension of the irradiated zone when a partial organ irradiation was implemented. Specific normalized coefficients for calculating the MGD to the whole breast or to the single irradiated slice were reported.